Socialization of the Use of Botanical Pesticides Based on Noni and Garlic in the Braja Asri Village Area, Way Jepara District, East Lampung Regency - Saputra, Yasminia Friska; Karmawati, Dede; Pratiwi, Tantri; Putri, Tasya Azzahra; Sari, Silvia Sinta; Ghifari, M. Anlian Fanza; Rofiq, Hud (Indonesian Journal of Community Services Cel, 2025)
Socialization is a process of interaction and learning carried out by the community with the aim of providing education related to matters that are not directly correlated with the learning process in schools. Many farmers in Braja Asri village use chemical pesticides to kill plant pests (OPT) which is the background for the socialization regarding the use of this botanical pesticide. The choice of noni as the basic ingredient for making pesticides is because many residents have noni fruit plants that are not used in their yards. In addition, additional ingredients in the form of garlic are also used in the process of making this botanical pesticide because it is easy to find. The implementation method for the KKN work program period II in 2024 at the University of Lampung is Participatory Rural Appraisal (PRA) in the form of an approach in the process of empowerment and increasing community participation that emphasizes community involvement in all activities carried out. The result is, as many as 30 people participated in this socialization activity until its completion.